Intranasal Midazolam May Prevent Gagging Reflex: a Case Report - Meral Arslan Malkoc; Necla Demir; Zehra Ileri; Aybuke Erdur; Seza Apiliogullari (Stilus Optimus, 2013)
Background: Gagging can become a conditioned response that makes dental treatment difficult or impossible for both the individual and the dentist. The aim of this study is to report a 50 year old female and two children (15 and 11 years old) with exaggerated gag reflex referred to Faculty of Dentistry of Selçuk University.Methods: During obtaining records, taking impression procedure was elicited the patients' hypersensitive gagging reflex. Therefore, it was decided to administer intranasal midazolam to facilitate the taking of accurate dental impressions. After given verbal information about the procedure, 2.5 mg intranasal midazolam (Demizolam, Dem Medikal, Istanbul) were applied incrementally in both nostrils.Results: Five minutes later; patients had no gagging reflex and allowed the clinician to take satisfying impressions. No serious adverse effects were observed and the patients remained cooperative during the entire procedure which was completed to the full satisfaction of all involved. The short absorption time and the fast relief process of anaesthetics transferred to the systemic circulatory system are important advantages of nasal application.Conclusions: Intranasal midazolam may be very useful for the treatment of gag reflex probably effecting on the depression of upper airway reflex sensitivity.